Getting in shape: habitat‐based morphological divergence for two sympatric fishes. (27th October 2014) - Foster, Kimberly; Bower, Luke; Piller, Kyle
<x xml:space="preserve">Abstract</x> Freshwater fishes often show large amounts of body shape variation across divergent habitats and, in most cases, the observed differences have been attributed to the environmental pressures of living in lentic or lotic habitats. Previous studies have suggested a distinct set characters and morphological features for species occupying each habitat under the steady–unsteady swimming performance model. We tested this model and assessed body shape variation using geometric morphometrics for two widespread fishes, Goodea atripinnis (Goodeidae) and Chirostoma jordani (Atherinopsidae), inhabiting lentic and lotic habitats across the Mesa Central of Mexico. These species were previously shown to display little genetic variation across their respective ranges. Our body shape analyses reveal morphometric differentiation along the same axes for both species in each habitat. Both possess a deeper body shape in lentic habitats and a more streamlined body in lotic habitats, although the degree of divergence between habitats was less for C. jordani. Differences in the position of the mouth differed between habitats as well, with both species possessing a more superior mouth in lentic habitats. These recovered patterns are generally consistent with the steady–unsteady swimming model and highlight the significance of environmental forces in driving parallel body shape differences of organisms in divergent habitats. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 114, 152–162.